Why does waste separation policy vary across different Chinese cities? A configurational analysis of the pilot scheme. (10th February 2021) - He, Chenyang; Fu, Yang
Abstract: This study aims to explain why different policy instruments are selected and how different configurations of factors influence the policy selection in waste management in China. Firstly, we perform content analysis with Nvivo 11 to illustrate the regional variance in policy instrument choice among the 46 cities selected as pilots to enforce the separation of municipal solid waste (MSW). While some local governments mainly resort to regulatory instruments, some others show inclination toward incentive instruments. The authors then explore the mechanisms shaping local government's policy instrument choice with the configurational approach of fussy-set Qualitative Comparative Analysis (fsQCA), which has been seldom conducted empirically. The analysis generates several significant implications for policy instrument choice in waste management in China. It reveals how combinations of factors influence the instrument choice, which is difficult for regression analysis to capture. Second, it identifies equifinal causal paths to both incentive and regulatory instruments. Third, the fsQCA analysis also demonstrates the asymmetry of causality. Highlights: A systematic content analysis of waste separation policies in 46 pilot cities in China is conducted. Different categories of waste separation policies are summarized and compared. A configurational approach is employed to explain why waste separation policies differ in the pilot cities. Implications for better waste separation policies and practices are provided.